Correction to the type locality of Tomopterna ahli (Deckert, 1938) (Anura: Pyxicephalidae), with the designation of a neotype - Channing, Alan; Becker, Francois (Zootaxa, 2019)
Deckert described a Tomopterna as Arthroleptella ahli from South Africa in 1938. We demonstrate that the type of Tomopterna ahli (Deckert, 1938) was actually collected in Namibia, and that this nomen is a senior synonym of Tomopterna damarensis Dawood & Channing, 2002. We designate a neotype for Tomopterna ahli (Deckert, 1938).